The Impact of Different Environmental Conditions on Cognitive Function: A Focused Review - Taylor, Lee; Watkins, Samuel L.; Marshall, Hannah; Dascombe, Ben J.; Foster, Josh (Frontiers in Physiology, 2016)
Cognitive function defines performance in objective tasks that require conscious mental effort. Extreme environments, namely heat, hypoxia, and cold can all alter human cognitive function due to a variety of psychological and/or biological processes. The aims of this Focused Review were to discuss; 1) the current state of knowledge on the effects of heat, hypoxic and cold stress on cognitive function, 2) the potential mechanisms underpinning these alterations, and 3) plausible interventions that may maintain cognitive function upon exposure to each of these environmental stressors. The available evidence suggests that the effects of heat, hypoxia and cold stress on cognitive function are both task and severity dependent. Complex tasks are particularly vulnerable to extreme heat stress, whereas both simple and complex task performance appear to be vulnerable at even at moderate altitudes. Cold stress also appears to negatively impact both simple and complex task performance, however, the research in this area is sparse in comparison to heat and hypoxia. In summary, this focused review provides updated knowledge regarding the effects of extreme environmental stressors on cognitive function and their biological underpinnings. Tyrosine supplementation may help individuals maintain cognitive function in very hot, hypoxic, and/or cold conditions. However, more research is needed to clarify these and other postulated interventions.